2021
DOI: 10.3390/ani11020300
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Range Use and Fearfulness in Free-Range Hens from Different Rearing Enrichments

Abstract: Inconsistency between the environments of indoor pullet rearing and adult outdoor housing may increase the fearfulness in free-range hens. Rearing enrichments and/or range use may reduce adult fearfulness. Hy-Line Brown® chicks (n = 1700) were reared inside across 16 weeks with three enrichment treatments: weekly changing novel objects, custom-designed perching/navigation structures, or no additional enrichments. Pullets were transferred to a free-range system at 16 weeks of age, with range access provided fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
9
1
Order By: Relevance
“…Although the WG is screened, it is subjected to more variable environmental conditions than the indoor area, which may cause some animals to perceive it with greater uncertainty. Previous research in free-range housing found negative association between range-use and fearfulness [26][27][28], although free-range area differs from our WG (i.e. no uncovered areas or access to grass).…”
Section: Winter Garden Presencecontrasting
confidence: 77%
“…Although the WG is screened, it is subjected to more variable environmental conditions than the indoor area, which may cause some animals to perceive it with greater uncertainty. Previous research in free-range housing found negative association between range-use and fearfulness [26][27][28], although free-range area differs from our WG (i.e. no uncovered areas or access to grass).…”
Section: Winter Garden Presencecontrasting
confidence: 77%
“…According to Hartcher et al ( 79), low range users whose total duration outside was 16.7 h over 13 days, had around 50% longer tonic immobility durations than high range users whose total duration outside was 142.5 h over the same period, suggesting a higher fearfulness in low ranger hens. However, this relationship between tonic immobility duration and range use has not been established in other studies (94,95). Fearfulness measured in an open-field test and in an emergence test was also higher in low ranger hens (92,94).…”
Section: Personality and Range Usementioning
confidence: 68%
“…However, this relationship between tonic immobility duration and range use has not been established in other studies (94,95). Fearfulness measured in an open-field test and in an emergence test was also higher in low ranger hens (92,94).…”
Section: Personality and Range Usementioning
confidence: 68%
“…2.2 Laying hen study 2.2.1 Ethics statement flock of free-range hens that had been reared in different enriched environments. The full experimental housing details for this study have been reported elsewhere (Campbell et al, 2020;Bari et al, 2021) and so are presented in brief here.…”
Section: Literature Reviewmentioning
confidence: 99%